Deixis Meaning in the Movie Sejuta Sayang Untuknya: A Kortara-Based Analysis - Dakhi, Epos Sister Krismon Selan (Austronesian: Journal of Language Science & Literature, 2025)
This study explores the use of deictic elements in the film Sejuta Sayang Untuknya through a technology-based approach utilizing the Kortara platform. Deixis, as a linguistic feature that relies on contextual information, plays a significant role in shaping the narrative and interactions within the film. The analysis focuses on personal deixis (e.g., saya, kamu, dia) and temporal deixis (e.g., sekarang, besok) to examine how these elements contribute to characterizations, relationships between characters, and the overall temporal structure of the storyline. The study reveals that deictic expressions serve as crucial tools for conveying emotional tones, power dynamics, and social hierarchies in dialogues. By applying Kortara, a computational tool designed for linguistic analysis, the study provides detailed insights into the frequency and distribution of deictic elements, offering a deeper understanding of how cultural and social contexts influence language use in cinematic discourse. This research highlights the potential of computational linguistics in analyzing pragmatics and social dynamics in film dialogues, contributing to both applied linguistics and the study of language in media. The findings underscore the importance of deictic elements as markers of personal and temporal relationships that shape the audience’s interpretation of character interactions and the narrative flow.